Sensory lexicon development using trained panelists in Thailand and the United States: soy sauce - Cherdchu, P.; Chambers, Edgar, IV; Suwonsichon, T. (My University, 2013)
Twenty soy sauce products were presented to two sensory panels, one in Thailand and one in the U.S. Both panels had extensive training conducting descriptive sensory studies. Neither group had tested soy sauce previously; however, they had different familiarity with soy sauce. Each group separately evaluated samples during the same time period; then met, in Thailand, to compare and discuss their generated lexicons. Most attributes listed by each group of panelists provided similar definitions and references. Although, a few attributes were not used by one or the other panel because that term either does not exist in both languages (e.g., “cured” is not a term for the Thai panel), represented an uncommon characteristic (e.g., “roaches” for the American panel), or were complex concepts (e.g., “brown”), the panelists used references to assist their understanding of unclear attributes. After discussion, both panels agreed on 59 attributes with definitions and references for a soy sauce lexicon. The paper presents attributes in English and Thai.
Keywords: Lexicon; Descriptive sensory analysis; Soy sauce; Trained panel